Multiplex fluorescent analysis of four short tandem repeats for rapid haemophilia A molecular diagnosis - Sánchez-García, Jorge F.; Gallardo, Dominique; Ramírez, Lorena; Vidal, Francisco (Thrombosis and Haemostasis, 2005)
Indirect molecular diagnosis of hemophilia A (HA) is carried out by analyzing intragenic polymorphic markers described along the coagulation factorVIII (FVIII) gene. Several studies have demonstrated that the two commonly used intronic short tandem repeats (STR13 and STR22) located in the FVIII gene are highly informative for this task. Two extragenic markers closely linked to FVIII (DXS1073 and DXS1108) have also been described as valuable tools for gene tracking. The objective of the present work was to develop a rapid, single-tube automated method to simultaneously analyze these four STRs. Consistent amplification was achieved by quadruplex fluorescent PCR and the products were analyzed by capillary electrophoresis. Validation of the method included DNA analysis of 88 individuals from a control population, 45 HA patients and 32 individuals from 10 HA-affected families. Statistical study showed that the STR13, STR22 and DXS1108 loci were in significant linkage disequilibrium, whereas DXS1073 was not. Nevertheless, the combination of the four markers offered a high heterozygosity rate (>90%) that improved tracing of FVIII gene inheritance. Optimal results with application to single cells in a HA preimplantation genetic diagnosis (PGD) protocol demonstrated the sensitivity of the technique. In conclusion, the automated fluorescent method described is an extremely rapid, simple and highly informative one that is easy to standardize and allows direct comparison of results among different groups working with genetic counseling, prenatal diagnosis and PGD in HA-affected families.
Keywords: STR; PGD; haemophilia A; factor VIII; linkage analysis